A description of students' commenting behaviours in an online blogging activity. (March 2021) - Cheng, Jiaming; Lei, Jing
Student-student interaction can benefit learning as well as provide a sense of community in online courses. Blogging is a common approach to provide opportunities for students to communicate with each other. This study used Social Network Analysis to depict commenting behaviour between students in an online graduate-level course. By examining the weekly interaction data, the results revealed how students' commenting behaviours changed during the semester. Student participation and interaction in the blogging activity was influenced by the various pedagogical elements that were either directly or indirectly related to the blogging activity.